2012
DOI: 10.1111/ans.12014
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral prostate resection for urinary retention: does age affect outcome?

Abstract: Outcome after TURP for urinary retention is satisfactory. Advanced age is associated with higher long-term failure requiring catheterization, although it is still recommended in the elderly where an anaesthetic is safe. A high proportion of patients report urine leakage but the majority of this is clinically insignificant. Overall, patients report good quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
3
6
0
1
Order By: Relevance
“…In contrast to a previous study , we found no correlation between patient age and reduction in symptoms after PAE. While in the TURP group in the trial, younger patients (<70 vs ≥70 years) had a more distinct improvement in IPSS, which is in line with previous studies on transurethral surgical techniques , this correlation was not found after PAE.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to a previous study , we found no correlation between patient age and reduction in symptoms after PAE. While in the TURP group in the trial, younger patients (<70 vs ≥70 years) had a more distinct improvement in IPSS, which is in line with previous studies on transurethral surgical techniques , this correlation was not found after PAE.…”
Section: Discussionsupporting
confidence: 89%
“…The mean percentage volume reduction observed in our PVP group (40%) was also slightly lower compared with the published results of BPH patients who underwent PVP with similar prostate volumes (43-72%) [18,19]. Our results revealed similar stress UI rates in both TURP (5.5%) and PVP (5.2%) in CaP patients compared with the literature data of BPH patients (1-5%) [22,23]. …”
Section: Discussionsupporting
confidence: 48%
“…Further, persistence of storage symptoms following TURP has been reported more frequently in men >80 years of age [3]. In another study of 100 consecutive patients who underwent TURP, a high proportion of patients reported increasing urine leakage with increasing age [9]. Knutson et al [10] reported that high age was an independent risk factor for coexisting detrusor overactivity in BPE.…”
Section: Discussionmentioning
confidence: 99%